APLICACIÓN DE BIOESTIMULANTES A BASE DE L-α-AMINOÁCIDOS EN EL CULTIVO DE PALMA ACEITERA (Elaeis Guineensis Jacq.) Y SU EFECTO EN LA EMISIÓN FOLIAR - Mueckay Guerrero , Rubén Darío (2023)
The research was conducted at "Angelita" estate, located in the district of "La Victoria," Quevedo Canton, Los Ríos Province, Ecuador. The estate covers an area of 20 hectares dedicated to the production of oil palm, specifically of the INIAP Tenera variety. The primary purpose was to evaluate the impact of using bio-stimulants containing L-α-amino acids on the leaf emission of the oil palm (Elaeis guineensis Jacq.). To carry out the study, a completely randomized block experimental design was implemented, which included four treatments (T1: 1 L/ha Armurox + 1 L/ha Equilibrium; T2: 2 L/ha Equilibrium; T3: 2 L/ha Terrasorb Complex; T4 Control) and was replicated five times.